2022
DOI: 10.1101/2022.04.21.489047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

rTg(TauP301L)4510 mice exhibit increased VGLUT1 in hippocampal presynaptic glutamatergic vesicles and increased extracellular glutamate release

Abstract: The molecular pathways that contribute to the onset of symptoms in tauopathy models, including Alzheimer’s Disease (AD), are difficult to distinguish because multiple changes can happen simultaneously at different stages of disease progression. Understanding early synaptic alterations and their supporting molecular pathways is essential in order to develop better pharmacological targets to treat AD. Here we focus on an early onset rTg(TauP301L)4510 tauopathy mouse model that exhibits hyperexcitability in hippo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…We recently demonstrated that Tau destabilization from MTs and its increased expression as a soluble MT-unbound protein, occurring at early stages of the disease, cause a significant increase in Tau nuclear levels, changing the expression of genes involved in synaptic transmission and leading to toxic hyperexcitability (Siano et al, 2019b). Accordingly, neuronal hyperexcitability, associated also with VGluT1 increase, has been identified as a hallmark of early AD pathology (Ghatak et al, 2019;Siano et al, 2020;Taipala et al, 2022). The molecular mechanisms mediating this effect are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that Tau destabilization from MTs and its increased expression as a soluble MT-unbound protein, occurring at early stages of the disease, cause a significant increase in Tau nuclear levels, changing the expression of genes involved in synaptic transmission and leading to toxic hyperexcitability (Siano et al, 2019b). Accordingly, neuronal hyperexcitability, associated also with VGluT1 increase, has been identified as a hallmark of early AD pathology (Ghatak et al, 2019;Siano et al, 2020;Taipala et al, 2022). The molecular mechanisms mediating this effect are still elusive.…”
Section: Discussionmentioning
confidence: 99%